Novel mechanism of sulfate erosion mitigation in cement mortar using CF-based densifier: microstructural and durability perspectives - Liu, Jianye; Huang, Peishan; Gan, Hehao; Wang, Xin; Liu, Zhuo (Frontiers in Materials, 2025)
Cementitious materials are widely used in marine and alkaline environments, where sulfate erosion resistance significantly influences structural durability and safety. To address this challenge, this study systematically evaluated the effectiveness of CF-S2 densifier in enhancing sulfate erosion resistance of cement mortar. The performance of CF-based densifier mortars with varying dosages was assessed by compressive strength, mercury intrusion porosimetry (MIP), SO42- concentration distribution, and dry-wet cyclic sulfate erosion tests. The results indicated that the CF-based densifier optimized the pore size distribution by reducing the proportion of harmful pores (≥100 nm), especially macropores (>1,000 nm). Meanwhile, it increased the proportion of transition pores (10–100 nm) and improved pore tortuosity, effectively hindering aggressive ion penetration. After 60 wet-dry cycles, compared to ordinary Portland cement (OPC) mortar, the compressive strength and corrosion resistance coefficient of mortar containing 0.1% CF-S2 increased by 36.4% and 41.5%, respectively, along with significantly reduced surface erosion damage. Moreover, SO42- concentration distribution tests showed consistently lower SO42- concentrations at all measured depths in densifier mortar, confirming improved sulfate resistance. This study demonstrates that CF-based densifier significantly enhances the mechanical properties and sulfate erosion resistance of cement mortar, providing an effective strategy for improving durability of cement-based materials and offering broad prospects for engineering applications.